The Role of Ziswaf To Improve Economic Equality in West Nusa Tenggara - Titin Agustina; Dewi Apriyani; Gaoz Rozi Fahraini; Siti Nur Hidayati (International Journal of Economics and Management Sciences, 2024)
This research aims to examine the role of ZISWAF (Zakat, Infaq, Sadaqah, and Waqf) in economic equality in the province of West Nusa Tenggara (NTB) using a qualitative approach. ZISWAF is seen as a financial instrument that has great potential for reducing economic disparities between community groups in NTB. A qualitative approach is used to understand the impact of ZISWAF's contribution to economic equality and the factors that influence its implementation. The research results show that ZISWAF has a significant role in economic equality in NTB. Through fund distribution, economic empowerment programs, and infrastructure development, ZISWAF can reduce economic disparities between community groups.